Identification of pathogens causing brown rot of stone fruit in Cuneo province (Italy) and assessment of sensitivity to azoxystrobin, cyprodinil, fenhexamid, fludioxonil, and tebuconazole - Greta DARDANI; Vladimiro GUARNACCIA; Luca NARI; Stefanos I. TESTEMPASIS; George S. KARAOGLANIDIS; M. Lodovica GULLINO (Phytopathologia Mediterranea)
Monilinia spp. cause brown rot and blossom blight of stone fruit. This study characterized the diversity of Monilinia spp. associated with stone fruit rots in the Cuneo province, the major fruit production area in Piedmont, and assessed their sensitivity to azoxystrobin, cyprodinil, fenhexamid, fludioxonil and tebuconazole. Species diversity was determined by PCR amplification and sequencing of isolate internal transcribed spacer (ITS) regions. Sensitivity to fungicides was determined by measuring in vitro mycelium growth on fungicide-amended media. Fifty isolates were obtained from apricot, cherry, or peach fruits with typical brown rot symptoms. Thirteen isolates were identified as M. fructicola, and 37 as M. laxa. Nine isolates of Monilinia laxa and two of M. fructicola had resistance factor (RF) values greater than 10 for different fungicides. The greatest (RF) value (48.96) was measured for azoxystrobin against the M. fructicola isolate CVG 1514. Among the M. laxa isolates, isolate CVG 1547 had the greatest RF value to cyprodinil, while isolate CVG 1709 had RF values greater than 10 for cyprodinil and tebuconazole. A systematic and wider sampling should be carried out in the Piedmont region to determine the distribution of fungicide resistant Monilinia spp. in stone fruit crops. The use of site-specific fungicides remains the most effective strategy for control brown rot, and continued monitoring for fungicide resistance within Monilinia spp. populations is recommended.